2023
DOI: 10.1002/advs.202206669
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial TSPO Promotes Hepatocellular Carcinoma Progression through Ferroptosis Inhibition and Immune Evasion

Abstract: Hepatocellular carcinoma (HCC) is one of the most common malignancies with poor prognosis, and novel treatment strategies are urgently needed. Mitochondria are key regulators of cellular homeostasis and potential targets for tumor therapy. Here, the role of mitochondrial translocator protein (TSPO) in the regulation of ferroptosis and antitumor immunity is investigated and the potential therapeutic implications for HCC are assessed. TSPO is highly expressed in HCC and associated with poor prognosis. Gain-and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…The MCL‐1 can be combined with Beclin 1 protein BH3 domain structure, thus inhibiting Beclin 1, autophagy and negative control cells 76–78 . In addition, the agglomeration of P62 and autophagy is directly related to, such as TSPO can through direct action with P62, lead to agglomeration of P62 and inhibition of autophagy 79 . In bladder cancer, CXCL12 upregulates the deubiquitinating enzyme CYLD through the JAK2/STAT3 signalling pathway, and CYLD inhibits autophagy in bladder cancer by inducing the accumulation of P62 through deubiquitination of P62 80 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MCL‐1 can be combined with Beclin 1 protein BH3 domain structure, thus inhibiting Beclin 1, autophagy and negative control cells 76–78 . In addition, the agglomeration of P62 and autophagy is directly related to, such as TSPO can through direct action with P62, lead to agglomeration of P62 and inhibition of autophagy 79 . In bladder cancer, CXCL12 upregulates the deubiquitinating enzyme CYLD through the JAK2/STAT3 signalling pathway, and CYLD inhibits autophagy in bladder cancer by inducing the accumulation of P62 through deubiquitination of P62 80 .…”
Section: Discussionmentioning
confidence: 99%
“… 76 , 77 , 78 In addition, the agglomeration of P62 and autophagy is directly related to, such as TSPO can through direct action with P62, lead to agglomeration of P62 and inhibition of autophagy. 79 In bladder cancer, CXCL12 upregulates the deubiquitinating enzyme CYLD through the JAK2/STAT3 signalling pathway, and CYLD inhibits autophagy in bladder cancer by inducing the accumulation of P62 through deubiquitination of P62. 80 In addition, through the JAK2/STAT3 signalling pathway inhibitor Stattic also can inhibit the rise in JAK2/STAT3 signal pathway of P62, 80 miR‐16‐5p can promote autophagy by upregulating Beclin 1 and downregulating P62, thus playing an inhibitory effect on bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The difference may be mainly due to the opposite regulatory direction of the two, such as the former upregulates ferroptosis resistance genes and reduces the incidence of ferroptosis, thereby reducing the production of immunogenic cell death, reducing the immunogenicity of tumor, and escaping the killing of immune cells. Recently, it has been reported that Mitochondrial translocator protein promotes tumor cell immune escape by up-regulating PD-L1 expression through Nrf2-mediated transcription ( 76 ).…”
Section: Dual Role Of Ferroptosis In Lung Cancermentioning
confidence: 99%
“…Unfortunately, the aforementioned therapies demonstrate low ability in significantly improving survival and prognosis of patients [86] , urging scientists for developing new therapies for HCC. Moreover, in the recent years, immunotherapy has been significantly applied in the treatment of cancer [ 87 , 88 ] that it is of importance for HCC, but the immune evasion is a problem in HCC therapy [89] , [90] , [91] .…”
Section: Hepatocellular Carcinoma: An Overviewmentioning
confidence: 99%